Some Aspects of Nonlinearity and Self-Organization In Biosystems on Examples of Localized Excitations in the DNA Molecule and Generalized Fisher–KPP Model; Symmetry; Vol. 10, iss. 3 - Shapovalov A. V. Aleksandr Vasilyevich (2018, 2018)
Title screen